Depletion of regulatory T cells enhancing the anti-tumor effect of in situ vaccination in solid tumors - Ya-Jia Xie; Sha Tian; Min Huang; Lin-Lin Lu; Zhong-Qiu Liu; Jun-Hui Chen; Xing-Xing Fan (Elsevier, 2024)
The emergence of immune checkpoint inhibitors (ICIs) has revolutionized the clinical treatment for tumor. However, the low response rate of ICIs remains the major obstacle for curing patients and effective approaches for patients with primary or secondary resistance to ICIs remain lacking. In this study, immune stimulating agent unmethylated CG-enriched (CpG) oligodeoxynucleotide (ODN) was locally injected into the tumor to trigger a robust immune response to eradicate cancer cells, while anti-CD25 antibody was applied to remove immunosuppressive regulatory T cells, which further enhanced the host immune activity to attack tumor systematically. The combination of CpG and anti-CD25 antibody obtained notable regression in mouse melanoma model. Furthermore, rechallenge of tumor cells in the xenograft model has resulted in smaller tumor volume, which demonstrated that the combinational treatment enhanced the activity of memory T cells. Remarkably, this combinational therapy presented significant efficacy on multiple types of tumors as well and was able to prevent relapse of tumor partially. Taken together, our combinational immunotherapy provides a new avenue to enhance the clinical outcomes of patients who are insensitive or resistant to ICIs treatments.